Peripheral Immune Cell Ratios and Clinical Outcomes in Seropositive Autoimmune Encephalitis: A Study by the Australian Autoimmune Encephalitis Consortium - Broadley, James; Wesselingh, Robb; Seneviratne, Udaya; Kyndt, Chris; Beech, Paul; Buzzard, Katherine; Nesbitt, Cassie; D’Souza, Wendyl; Brodtmann, Amy; Kalincik, Tomas; Butzkueven, Helmut; O’Brien, Terence J.; et al. (Frontiers in Immunology, 2021)
Objective: To examine the utility of the peripheral blood neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-lymphocyte ratio (MLR) as biomarkers of prognosis in seropositive autoimmune encephalitis (AE). Methods: In this multi-center study, we retrospectively analyzed 57 cases of seropositive AE with hospital admissions between January 2008 and June 2019. The initial full blood examination was used to determine each patients’ NLR and MLR. The modified Rankin Scale (mRS) was utilized to assess the patients’ follow-up disability at 12 months and then at final follow-up. Primary outcomes were mortality and mRS, while secondary outcomes were failure of first line treatment, ICU admission and clinical relapse. Univariate and multivariable regression analysis was performed. Results: During initial hospital admission 44.7% of patients had unsuccessful first line treatment. After a median follow-up of 700 days, 82.7% had good functional outcome (mRS ≤2) while 5 patients had died. On multivariable analysis, high NLR was associated with higher odds of first line treatment failure (OR 1.32, 95%CI 1.03-1.69, p=0.029). Increased MLR was not associated with any short or long-term outcome. Conclusions: NLR on initial hospital admission blood tests may be provide important prognostic information for cases of seropositive AE. This study demonstrates the potential use of NLR as a prognostic marker in the clinical evaluation of patients with seropositive AE.